The Logarithmic Transform of a Polynomial Function Expressed in Terms of the Lerch Function - Robert Reynolds; Allan Stauffer (Mathematics, 2021)
This is a collection of definite integrals involving the logarithmic and polynomial functions in terms of special functions and fundamental constants. All the results in this work are new.